The More Internet Access, the More Mental Symptoms Students Got, the More Problematic Internet Use They Suffered: a Meta-analysis of Mainland Chinese Adolescents and Young Adults. - Li, Shunyu; Wang, Xiaotong; Wu, Zhili; Zhang, Yuxuan (International Journal of Mental Health & Addiction, 2023)
The traditional view is that mental symptoms and problematic Internet use are positively related. Still, other researchers have questioned this view, and they believe that mental symptoms are negatively associated with problematic Internet use. Since then, this controversy has continued yet. The current study attempts to use meta-analysis to explore the relationship between mental symptoms and problematic Internet use in mainland Chinese students to provide a reliable basis for resolving this dispute. Sixty-three articles were included in this study, including 66 sample sizes and 47,968 subjects. It found that mental symptoms are positively correlated with problematic Internet use (r =.288, 95% confidence interval [.255,.320]). The correlation is affected by regions. Compared with coastal areas, problematic Internet users in the non-coastal areas are more likely to be affected by mental symptoms. In addition, gender differences also significantly affect the relationship between mental symptoms and problematic Internet use. The correlation coefficient between mental symptoms and problematic Internet use of girls is significantly higher than that of boys. Moreover, year also significantly affects the relationship between mental symptoms and problematic Internet use—the correlation increases by growing years.